Analisis Konsumsi Energi Karyawan Ketika Melakukan Olahraga Tenis: Studi Kasus Karyawan PT. Aker Solution Batam - Elva Susanti; Welly Sugianto; Zefri Azharman (Universitas Putera Batam, 2018)
This study aims to find the level of energy consumption, CVR% and Boddy mass index through the pulse before and after sports. In calculation of CVR% there are 4 people needed improvement, 1 person must reduce the activity time so as not to injury while doing sports. In determining the heartbeat pulse (pulse) by testing the wilxocon turns out the higher heart rate before exercising, the higher the heart rate after exercise or vice versa. In addition, by doing chi square test between energy consumption with obesity has nothing to do.